Specific features of adaptation of rats to chronic cold treatment; Doklady Biological Sciences; Vol. 470, iss. 1 - Tsibulnikov S. Yu. Sergey Yurjevich; Maslov L. N. Leonid Nikolaevich; Naryzhnaya N. V. Nataliya Vladimirovna; Ivanov V. V. Vladimir Vladimirovich; Lishmanov Yu. B. Yury Borisovich (2016, 2016)
Title screen